2020
DOI: 10.1186/s12944-020-01352-1
|View full text |Cite
|
Sign up to set email alerts
|

A minor allele of the haplotype located in the 19q13 loci is associated with a decreased risk of hyper-LDL-cholesterolemia, and a balanced diet and high protein intake can reduce the risk

Abstract: Background Although the human chromosome 19q13 loci are reported to be associated with hyper-LDL-cholesterolemia, the haplotype of single nucleotide polymorphism (SNP) has not been studied. Therefore, the association of the haplotype in 19q13 loci with hyper-LDL-cholesterolemia was determined and their interactions with lifestyles and nutrient intakes were evaluated in 28,445 Koreans aged > 40 years. Methods SNPs were selected from 19q13 loci that had an association wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…We determined the number of factors based on eigenvalues >1.5, and 3 dietary factors described the distinct dietary-pattern in the participants. The orthogonal rotation procedure (varimax) was applied in the principal component analysis (PCA), and factor-loading values ≥0.40 were considered to have dominant contributions to the distinctive dietary pattern ( Table 1 ) [ 20 ]. Using clustering analysis (proc fastclus), the adults were divided into three cluster groups by calculating the distance from the assigned point after standardization of the data by proc stdize.…”
Section: Methodsmentioning
confidence: 99%
“…We determined the number of factors based on eigenvalues >1.5, and 3 dietary factors described the distinct dietary-pattern in the participants. The orthogonal rotation procedure (varimax) was applied in the principal component analysis (PCA), and factor-loading values ≥0.40 were considered to have dominant contributions to the distinctive dietary pattern ( Table 1 ) [ 20 ]. Using clustering analysis (proc fastclus), the adults were divided into three cluster groups by calculating the distance from the assigned point after standardization of the data by proc stdize.…”
Section: Methodsmentioning
confidence: 99%
“…The 103 food items in the SQFFQ were categorized into 29 predefined food groups [ 14 , 15 ]. The food groups were used as independent variables during factor analysis conducted to find dietary patterns using the FACTOR procedure.…”
Section: Methodsmentioning
confidence: 99%
“…We determined the number of factors to retain using eigenvalues of >1.5 and 4 dietary factors describing the distinct dietary patterns of participants. The orthogonal rotation procedure (varimax) was applied during principal component analysis [ 14 ]. Factor-loading values ≥0.40 were considered to make primary contributions to distinct dietary patterns ( Supplemental Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies indicated TOMM40 was genetically associated with cardiovascular-related traits ( 214 , 215 , 229 , 230 ). Several genome-wide association studies (GWAS) have identified that the TOMM40/APOE locus was strongly associated with low-density lipoprotein cholesterol [rs157580 ( 231 )], high-density lipoprotein cholesterol [rs2075650, ( 232 ), rs157581 ( 233 )], high-sensitivity C-reactive protein [rs2075650 ( 234 )], type 2 diabetes [rs157580 ( 231 )], or metabolic syndrome ( 235 ). Additionally, experimental evidence showed that homozygous deletion of TOMM40 in mammals was lethal, and heterozygous TOMM40 knockdown mice were found to have cardiac arrhythmia that deteriorated with age ( 236 ).…”
Section: Mitochondrial Protein Import Machinery and Heart Diseasementioning
confidence: 99%